Deficiency of Thrombospondin-4 in Mice Does Not Affect Skeletal Growth or Bone Mass Acquisition, but Causes a Transient Reduction of Articular Cartilage Thickness - Jeschke, Anke; Bonitz, Martin; Simon, Maciej; Peters, Stephanie; Baum, Wolfgang; Schett, Georg; Ruether, Wolfgang; Niemeier, Andreas; Schinke, Thorsten; Amling, Michael (PLoS ONE, 2015)
Although articular cartilage degeneration represents a major public health problem, the underlying molecular mechanisms are still poorly characterized. We have previously utilized genome-wide expression analysis to identify specific markers of porcine articular cartilage, one of them being Thrombospondin-4 (Thbs4). In the present study we analyzed Thbs4 expression in mice, thereby confirming its predominant expression in articular cartilage, but also identifying expression in other tissues, including bone. To study the role of Thbs4 in skeletal development and integrity we took advantage of a Thbs4-deficient mouse model that was analyzed by undecalcified bone histology. We found that Thbs4-deficient mice do not display phenotypic differences towards wildtype littermates in terms of skeletal growth or bone mass acquisition. Since Thbs4 has previously been found over-expressed in bones of Phex-deficient Hyp mice, we additionally generated Thbs4-deficient Hyp mice, but failed to detect phenotypic differences towards Hyp littermates. With respect to articular cartilage we found that Thbs4-deficient mice display transient thinning of articular cartilage, suggesting a protective role of Thbs4 for joint integrity. Gene expression analysis using porcine primary cells revealed that Thbs4 is not expressed by synovial fibroblasts and that it represents the only member of the Thbs gene family with specific expression in articular, but not in growth plate chondrocytes. In an attempt to identify specific molecular effects of Thbs4 we treated porcine articular chondrocytes with human THBS4 in the absence or presence of conditioned medium from porcine synovial fibroblasts. Here we did not observe a significant influence of THBS4 on proliferation, metabolic activity, apoptosis or gene expression, suggesting that it does not act as a signaling molecule. Taken together, our data demonstrate that Thbs4 is highly expressed in articular chondrocytes, where its presence in the extracellular matrix is required for articular cartilage integrity.
EVALuna2:13177